An overview on avian influenza - Martins,Nelson Rodrigo da Silva (2012)
Avian influenza (AI) is considered an exotic disease in the Brazilian poultry industry, according to the National Avian Health Program (PNSA), with permanent monitoring of domestic, exotic and native avian species. Brazil presents privileged environmental conditions of reduced risk. In addition, all commercial poultry and conservation holdings are registered in state or national inventories and geographically located (GPS) for health control. Poultry health standards are adopted for the conformity to the international market, mostly for the intensified poultry destined for exportation, but also for companion exotic and native conservation facilities. Guidelines for monitoring and the diagnosis of AI are published by the PNSA and follow the standards proposed by the international health code (World Organization for Animal Health, Organization International des Epizooties - OIE) and insure the free of status for avian influenza virus (AIV) of LPAIV-low pathogenicity AIV and HPAIV-high pathogenicity AIV. In addition, the infections by mesogenic and velogenic Newcastle disease virus, Mycoplasma gallisepticum, M. synoviae and M. meleagridis, Salmonella enteric subspecies enterica serovar Gallinarum biovars Gallinarum and Pullorum are eradicated from reproduction. Controlled infections by S.enterica subspecies enterica serovars Enteritidis and Typhimurium are monitored for breeders. The vaccination of chickens in ovo or at hatch against Marek's disease is mandatory. Broiler production is an indoor activity, confinement which insures biosecurity, with safe distances from the potential AIV reservoir avian species. Worldwide HPAIV H5N1 notifications to the OIE, in March 2011, included 51 countries.